Give Please a Chance - O'Reilly, Bill; Patterson, James 1947-; Magoon, Scott (New York : Jimmy Patterson Books/Little, Brown and Company, 2016)
"In this illustrated book written by bestselling authors Bill O'Reilly and James Patterson, a collection of artists each contribute a piece of art demonstrating why the word 'please' makes all the difference in the world"--
Keywords: Etiquette -- Juvenile fiction; Etiquette -- Fiction